2015
DOI: 10.3390/molecules200916933
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Resveratrol Derivatives as Melanogenesis Inhibitors

Abstract: Resveratrol (1), a naturally occurring stilbene compound, has been suggested as a potential whitening agent with strong inhibitory activity on melanin synthesis. However, the use of resveratrol in cosmetics has been limited due to its chemical instability and poor bioavailability. Therefore, resveratrol derivatives were prepared to improve bioavailability and anti-melanogenesis activity. Nine resveratrol derivatives including five alkyl ether derivatives with C2H5, C4H9, C5H11, C6H13, and C8H17 (2a-2e) and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
(39 reference statements)
1
26
0
Order By: Relevance
“…Thus, five novel alkyl ether (ethyl, butyl, pentyl, hexyl and octyl) derivatives of Res were recently prepared which increased bioavailability compared to Res. Significantly, these derivatives retained the pharmacodynamic (melanogenesis inhibition) effect of Res evaluated (60) so that a mixture of Res and Alkyl-O-Res could be formulated to have both immediate and more prolonged biological activity based on rate of metabolic elimination and unmasking of antioxidant phenolic groups over time. In this respect, the metabolism of the ethyl ether would be more rapid than with any of the other alkyl ethers, with O-deoctylation being the slowest P450-catalyzed reaction in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, five novel alkyl ether (ethyl, butyl, pentyl, hexyl and octyl) derivatives of Res were recently prepared which increased bioavailability compared to Res. Significantly, these derivatives retained the pharmacodynamic (melanogenesis inhibition) effect of Res evaluated (60) so that a mixture of Res and Alkyl-O-Res could be formulated to have both immediate and more prolonged biological activity based on rate of metabolic elimination and unmasking of antioxidant phenolic groups over time. In this respect, the metabolism of the ethyl ether would be more rapid than with any of the other alkyl ethers, with O-deoctylation being the slowest P450-catalyzed reaction in this series.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin and vanillic acid inhibited α-MSH induced the expression of MITF, tyrosinase, TRP-1, and TRP-2, causing melanogenesis inhibition [35, 36]. Resveratrol derivatives inhibited melanin synthesis through the inhibition of melanogenic enzyme expressions such as tyrosinase and TRP-1 [37]. Our results indicated that K36E inhibited tyrosinase activity and α-MSH-induced protein expression, thereby suppressing melanin biosynthesis.…”
Section: Discussionmentioning
confidence: 85%
“…WING to its therapeutic and protective role, resveratrol [3,5,4'-trihydroxystilbene (RSV) (Figure 1a)] came into focus of research in recent years. Among numerous health benefits, RSV improves cardioprotection, cancer prevention and therapy, immune regulation and metabolic and neuroprotective functions.…”
Section: Introductionmentioning
confidence: 99%
“…[1−3] In order to enhance its activity, RSV was derivatized by: (i) modification of the number and position of the phenolic groups, (ii) insertion of a long alkyl chains or functionalized chains [4] and (iii) the addition of acyl chains to free hydroxyl groups. [5] The improved biological activity of the so-obtained RSV derivatives in comparison to those of the parent molecule is likely to be due to their lipophilicity and facilitated transport through cell membrane. Recently, RSV-derivatives I and II containing lipophilic ferrocene moiety instead of one benzene ring were synthesized (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%